Influence of intentional ankylosis of deciduous canines to reinforce the anchorage for maxillary protraction - Tocci,Luís Fernando Castaldi (2013)
INTRODUCTION: This retrospective cephalometric study analyzed the influence of intentional ankylosis of deciduous canines in patients with Class III malocclusion and anterior crossbite, in the deciduous and early mixed dentition stages, treated by orthopedic maxillary expansion followed by maxillary protraction. METHODS: Lateral cephalograms of 40 patients were used, divided in 2 groups paired for age and gender. The Ankylosis Group was composed of 20 patients (10 boys and 10 girls) treated with induced ankylosis and presenting initial and final mean ages of 7 years 4 months and 8 years 3 months, respectively, with a mean period of maxillary protraction of 11 months. The Control Group comprised 20 patients (10 boys and 10 girls) treated without induced ankylosis, with initial and final mean ages of 7 years 8 months and 8 years 7 months, respectively, with a mean period of maxillary protraction of 11 months. Two-way analysis of variance and covariance analysis were applied to compare the initial and final cephalometric variables and the treatment changes between groups. RESULTS: According to the results, the variables evidencing the significant treatment changes between groups confirmed that the intentional ankylosis enhanced the sagittal response of the apical bases (Pg-NPerp) and increased the facial convexity angles (NAP and ANB). CONCLUSIONS: The protocol involving intentional ankylosis of deciduous canines enhanced the sagittal response of the apical bases.